Content Aware Segment Length Optimization for Adaptive Streaming over HTTP - Zach, Ondrej; Slanina, Martin (Společnost pro radioelektronické inženýrství, 2018)
HTTP adaptive streaming is a widely used method for delivering the video content to its final recipi ents. The visual quality of the streamed video content is being adaptively changed according to network conditions to offer the user a smooth playback, which is even more impor tant for mobile connection like LTE. In this paper, we focus on the encoding the video content and on the segmentation of the video to be used in DASH based service. We used long sequences with duration up to 2.5 hours to simulate a real life situation. We investigate the influence of the GOP length on the final DASH segment size and evaluate the per formance of AVC and HEVC when used in DASH. We used several fixed values of GOP length and one special case of scene change based GOP creation. Our results showed, that such an adaptive segmentation mode brings up to 11% bi- trate savings with preserving comparable quality and lower fluctuations in absolute size of the DASH segments.
Keywords: Adaptive segmentation; GOP; group of pictures; H.264/AVC; H.265/HEVC; HTTP adaptive streaming; PSNR; video encoding